2016
DOI: 10.1002/cctc.201600072
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of Titania‐Supported Gold Nanoparticles Prepared by a Modified Deposition/Precipitation Method for the Oxidation of CO

Abstract: Supporting Information and the ORCID identification number(s) for the author(s) of this article can be found underh ttp://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 97 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…UV-vis spectra are exhibited in Figure 1. Visible light absorption of TiO 2 photocatalysts remarkably enhance with the increase of the gold percentage, due to the surface plasmon resonance (SPR) effect of Au-NPs, indicating that the metallic Au exists in the sample, as already confirmed in XPS analysis and DRIFTS analysis [14]. The visible light absorption of Au-NPs culminates in a broad response, ranging from 450 to 700 nm, which is possibly due to size distribution of Au-NPs.…”
Section: Dr Uv-vis Spectramentioning
confidence: 53%
See 2 more Smart Citations
“…UV-vis spectra are exhibited in Figure 1. Visible light absorption of TiO 2 photocatalysts remarkably enhance with the increase of the gold percentage, due to the surface plasmon resonance (SPR) effect of Au-NPs, indicating that the metallic Au exists in the sample, as already confirmed in XPS analysis and DRIFTS analysis [14]. The visible light absorption of Au-NPs culminates in a broad response, ranging from 450 to 700 nm, which is possibly due to size distribution of Au-NPs.…”
Section: Dr Uv-vis Spectramentioning
confidence: 53%
“…Morphologic and electronic characterizations have been widely reported elsewhere [14]. Briefly, high-resolution transmission electron microscopy (HRTEM) and scanning transmission electron microscopy (STEM) have confirmed that adopting the deposition-precipitation method led to very narrow gold particle size distribution fitted by a log-normal curve, with a mean diameter between 3.7 and 4.6 nm.…”
Section: Morphologic and Electronic Characterizationmentioning
confidence: 89%
See 1 more Smart Citation
“…The conversion of methanol on gold catalysts without photostimulation and in the absence of other reagents is less studied. Some work on steam reforming and methanol oxidation has been performed by using gold supported usually on various oxides. Herein we describe the ability of gold/zinc oxide catalysts to convert methanol under moderate conditions to mixtures of hydrocarbons, a surprising result because neither gold nor zinc oxide have any noteworthy tendencies to promote carbon−carbon bond formation except at high pressures of syngas.…”
Section: Resultsmentioning
confidence: 99%
“…Supported gold nanoparticles exhibit outstanding catalytic properties when deposited on titanium dioxide [37] [38]. The major problem with a gold based catalyst is the deactivation during the catalytic reaction; this phenomenon is often attributed to the agglomeration of gold nanoparticle [39] and sintering [40].…”
mentioning
confidence: 99%